2010
DOI: 10.1111/j.1439-0272.2010.01116.x
|View full text |Cite
|
Sign up to set email alerts
|

Sources of the porcine testis innervation

Abstract: This study was carried out on three adult male pigs of the large White Polish breed weighing 110-130 kg each. The animals were anaesthetised and injected with retrograde tracer Fast Blue (FB) into right testis. Three weeks later, the pigs were deeply anaesthetised and perfused transcardially with fixative (4% paraformaldehyde in 0.1 M phosphate buffer pH 7.4). Collected ganglia were cut with freezing microtome into 12-μm-thick sections. The sections were examined under a fluorescent microscope (Zeiss). FB-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
1
7
1
Order By: Relevance
“…27 In contrast to the distal colon, the guinea pig rectum was innervated by both lumbar and sacral spinal afferent neurons, with a distinctive bimodal distribution. This pattern of innervation is similar to that described previously for pelvic organs including mouse colorectum 28,29 rat colorectum, [30][31][32] pig bladder, 33 porcine testis, 34 porcine vas deferens 35 , and mouse uterus. 36 Thoraco-lumbar spinal afferents probably reach the rectum by projecting caudally via hypogastric nerves 37,38 to pelvic ganglia, then into the bowel via rectal nerves.…”
Section: Discussionsupporting
confidence: 87%
“…27 In contrast to the distal colon, the guinea pig rectum was innervated by both lumbar and sacral spinal afferent neurons, with a distinctive bimodal distribution. This pattern of innervation is similar to that described previously for pelvic organs including mouse colorectum 28,29 rat colorectum, [30][31][32] pig bladder, 33 porcine testis, 34 porcine vas deferens 35 , and mouse uterus. 36 Thoraco-lumbar spinal afferents probably reach the rectum by projecting caudally via hypogastric nerves 37,38 to pelvic ganglia, then into the bowel via rectal nerves.…”
Section: Discussionsupporting
confidence: 87%
“…Bilateral ganglia show tendency to fuse, forming the impaired structure in the pig and horse or 1-4 groups of neurons in the cat (Nickel et al 2004). The data regarding the pig are in contrast to our previous studies involving tracer investigations of genital organs and dealing with immunohistochemical properties of neurones innervating these organs (Kaleczyc et al 1994, Kaleczyc et al 1995, Kaleczyc 1998, Klimczuk and Kaleczyc 2010, Sienkiewicz 2010b. In these studies we always found the CaMG as the paired structure.…”
Section: Discussioncontrasting
confidence: 53%
“…Our present data are focused on the sensory ganglia, but we have done some preliminary investigation of gene expression in parts of the mouse brain and found results consistent with the human data represented in the Su submission. It is important to note that pancreas (Schwartz et al 2011), adipocytes (Bartness and Bamshad 1998;Osaka et al 1998), and testes (Sienkiewicz 2010) have significant interaction with dorsal root ganglia. These tissues in the mouse are reportedly regulated by OC that presumably originates from osteoclastic bone resorption (Ferron et al 2008;Ferron et al 2010;Lee et al 2007;Oury et al 2011).…”
Section: Discussionmentioning
confidence: 99%